The effect of the judge's condition on the judgment of others' well-being - Ganzach, Yoav (The Journal of social psychology, 2024)
We study the effect of perceivers' health conditions on their judgments of the well-being of target people (their judgments of the targets' day-to-day physical difficulties) based on information about the targets' health conditions. We develop a model which suggests that this effect depends on the similarity between perceivers' and targets' health: The perceiver's well-being is used as an anchor and the judgment of the target's well-being is either assimilated toward or contrasted away from this anchor, depending on the similarity between the subject's and target's health. Based on this model we derive and test the correlation-trend hypothesis which states that the higher the similarity between perceivers' and targets' conditions, the more positive the correlation between perceivers' conditions and their judgments of the targets well-being.